Development of Knowledge Economy Framework in the Life Science Sector in the Kingdom of Saudi Arabia - , (2018)
Natural resources-based income economies (Rentier economies) often suffer from a weak productive manufacturing base and low revenue and tax generation from these products and services. The prices of natural resources, such as oil and gas, change and fluctuate over time which poses a risk to national income and impedes the development of longer-term diversification/innovation strategies. It is these conditions which provide the context of this research into the current national policies to develop the “high value added” life sciences sector in the Kingdom of Saudi Arabia (KSA). This study adopts a grounded theory approach to the national innovation systems for the life sciences sector in the KSA. Little is known about the models employed and the current state of system development for the country and whether it varies from other such models. An initial literature review to frame the study was conducted on Innovation models to form a conceptual framework (India, Singapore, Taiwan, and South Korea). Field research was conducted and later a second systematic literature review was used to build theory and test the similarities/differences with the emerging KSA model (created by political, social, economic and industrial contingencies). The guiding research questions were:- What are the key requirements in developing knowledge economy (KE) in the life science (LS) sector in KSA?- What are the challenges in developing knowledge economy (KE) in LS in the KSA?- What model of innovation system best fits the Saudi context?Semi-structured in depth interviews (purposive sample) were conducted with senior stakeholders in the life science sector (government, private sector, and academia, ministry of health) to develop new theory. Through a three-stage open coding process including axial coding and selective coding, the findings revealed the challenges for developing an innovative LS system in Saudi Arabia. A questionnaire was developed to triangulate the earlier findings. The study finds that the KSA model differs from existing Innovation Models (India, Singapore, South Korea, and Taiwan) and creates a new insight into innovation in an Islamic context. It is recommended that this model be tested against similar contexts like Arabic Gulf countries (GCC) in future work.